GENDER DIFFERENCES IN UPPER LIMB MOTOR RECOVERY POST-STROKE: EFFECTS OF TASK-ORIENTED TRAINING AND REPETITION COUNTS (Journal of Biomedical Investigation, 2024)
Background: Stroke often results in significant impairments in upper limb motor function and daily activities, requiring various rehabilitation approaches. Constraint-Induced Movement Therapy and Task-Oriented Training are recognized interventions, but their efficacy may vary based on gender differences and repetition frequency.Aim: To investigate gender differences in upper limb motor rehabilitation post-stroke, focusing on the effects of task-oriented training and repetition counts.Methods: Stroke patients without severe motor or cognitive impairments were included in the study. Demographic and clinical data were collected, and upper limb motor function was assessed using the Motor Activity Log (MAL) and the Wolf Motor Function Test (WMFT). Participants performed a task involving the transfer of small wooden blocks between compartments for one hour, with the number of repetitions recorded every 15 minutes. Chi-square tests were used to examine relationships between variables and predict task repetition ability. The significance level was set at ≤ 0.05.Results: Among 75 participants (40 males, 35 females, aged 19-98), males completed slightly more task repetitions (53.3% vs. 46.7%). Participants averaged 437.50 task repetitions (range: 15-590). Statistical analysis showed no significant association between gender and the number of task repetitions (P > 0.05).Conclusion: The study found a strong correlation between WMFT and MAL in assessing upper limb impairment across both genders. Understanding gender-specific responses to task-oriented exercises and optimal repetition counts is essential for developing tailored rehabilitation strategies.
Keywords: Stroke rehabilitation; Motor function; Task-oriented exercises; Gender differences; Repetition counts